Case Studies: Effective Approaches for Navigating Cross-Border Cloud Data Transfers Amid U.S. Government Privacy and Safety Concerns - Adebayo, Motunrayo (European Journal of Applied Sciences, 2024)
This study attempts to explain the impact of information exchange from one country to another, as well as the legal and technological implications for these exchanges. Due to the emergence of cloud technology, possibilities for free exchange of information between countries have increased rapidly, as it has become possible to save information in a country and access it in almost any part of the world. Countries all around the world have been confronted with developing frameworks to facilitate this process, although there are significant challenges which must be confronted on legal and technological fronts, as loopholes in the framework adopted by countries may hinder free access to information stored on cloud, and also compromise data privacy. Cloud technology is impacting a lot of issues, including domestic and international businesses, hence the need for a study to propose measures for safe exchange of information using cloud technology.